EEG-based major depressive disorder recognition by neural oscillation and asymmetry - Liu, Xinyu; Zhang, Haoran; Cui, Yi; Zhao, Tong; Wang, Bin; Xie, Xiaomeng; Liang, Sixiang; Sha, Sha; Yan, Yuxiang; Zhao, Xixi; Zhang, Ling (Frontiers in Neuroscience, 2024)
Background: Major Depressive Disorder (MDD) is a pervasive mental health issue with significant diagnostic challenges. Electroencephalography (EEG) offers a non-invasive window into the neural dynamics associated with MDD, yet the diagnostic efficacy is contingent upon the appropriate selection of EEG features and brain regions. Methods: In this study, resting-state EEG signals from both eyes-closed and eyesopen conditions were analyzed. We examined band power across various brain regions, assessed the asymmetry of band power between the hemispheres, and integrated these features with clinical characteristics of MDD into a diagnostic regression model. Results: Regression analysis found significant predictors of MDD to be beta2(16-24Hz) power in the Prefrontal Cortex (PFC) with eyes open (B=20.092, p=0.011), beta3(24-40Hz) power in the Medial Occipital Cortex (MOC) (B=-12.050, p<0.001), and beta2 power in the Right Medial Frontal Cortex (RMFC) with eyes closed (B=24.227, p<0.001). Asymmetries in beta1(12-16Hz) power with eyes open (B=28.047, p=0.018), and in alpha (8-12Hz, B = 9.004, p=0.013) and theta (4-8Hz, B=-13.582, p=0.008) with eyes closed were also significant predictors.The study confirms the potential of multi-region EEG analysis in improving the diagnostic precision for MDD. By including both neurophysiological and clinical data, we present a more robust approach to understanding and identifying this complex disorder.The research is limited by the sample size and the inherent variability in EEG signal interpretation. Future studies with larger cohorts and advanced analytical techniques are warranted to validate and refine these findings.